Words Representation of Postfeminism in Indonesian Heroine Character : Case Study of Valentine Film - Daniar Wikan Setyanto; Santosa Soewarlan; Sumbo Tinarbuko (Pascasarjana Institut Seni Indonesia Surakarta, 2019)
The heroine is a character who has succeeded in embracing the public imagination in terms of self-image and became the ideal image of female, including in Indonesia. The character of Srimaya/ Valentine is a heroine character coming from local comic taken into Indonesia’s movies. The image presented on Srimaya/ Valentine is the symptom of capitalism in the Indonesian’s movies, the character is also one of the case studies in image reconstruction product or the representation of female using their image as a heroine. The discourse of female representation in the character of Srimaya/ Valentine does not only show about image idealized however it also represents the ideology of post-feminism as well as a politic of identity presented in the world of local films. The achievement of identity exceeds physical image from female because, in character, there are many symbols about feminists. This research was done to know the discourse of identity in view of post-feminism delivered in the film of Valentine(2017).